An updated combined biomass index of abundance for north Atlantic swordfish stock 1963-2012 - Ortiz, Mauricio; Mejuto-García, Jaime; Andrushchenko, Irene; Yokawa, Kotaro; Walter, J.; Neves-Santos, Miguel; Abid, N. (2014)
Surplus Production Models of North Atlantic swordfish have been used in addition to age structured virtual population analyses by ICCAT's SCRS to evaluate the status of the resource and to provide a basis for management advice. Production models require a standardized index of relative abundance in terms of biomass. The standardized biomass index of abundance developed for the 2006 and 2008 ICCAT-SCRS meetings for North Atlantic swordfish was revised and updated with data through 2012. Generalized Linear Modeling (GLM) procedures were used to standardize swordfish catch (biomass) and effort (number of hooks) data from the major longline fleets operating in the North Atlantic; United States, Spain, Canada, Japan, Morocco and Portugal. As in past analyses, main effects included: year, area, quarter, a nation-operation variable accounting for gear and operational differences thought to influence swordfish catchability, and a target variable to account for trips where fishing operations varied according to the main target species. Interactions among main factors were also evaluated.